Screening the Scars : The Cinematic (in)visibility of Social Trauma. - Hamburger, Andreas (Karnac Books, 2024)
Using the cultural medium of film to show how very differently social trauma is negotiated and narrated in different societies. A varied group of international experts offer a careful analysis of the psycho-historical roots of differently motivated losses of trust in social instances in connection with the concept of social trauma.
Keywords: Psychic trauma in motion pictures.; Collective trauma.; Traumatisme psychique au cinéma.; Film & Video.; PERFORMING ARTS.; Electronic books.